Historyblogosphere. Bloggen in den Geschichtswissenschaften - Haber, Peter (De Gruyter, 2013)
For the first time in the German language historical disciplines, a book has been subject to open peer review as it was developed. All contributions were discussed online with comments. The 'history blogosphere' has thereby engaged in understanding an especially timely topic- namely, the medium of the blog itself.